Predictor scales of cognitive factors affecting physical activity in individuals surviving cancer: psychometric properties of Turkish versions - Kaya, Şura; Esin, Melek Nihal (My University, 2025)
Background: Increasing physical activity in individuals surviving cancer is crucial in reducing treatment-related side effects and recurrence. Valid and reliable measurement tools are needed that will enable the factors affecting exercise to be addressed holistically and theoretically. This study aimed to adapt the Exercise Goal-Setting Scale, Exercise Planning and Scheduling Scale, Multidimensional Outcome Expectations for Exercise Scale, and Physical Activity Neighborhood Environment Scale into Turkish language and to explore psychometric properties of the Turkish versions of these scales in individuals surviving cancer. Methods: This methodologically designed research collected data from 153 participants at a hospital in Istanbul, Türkiye. The scales used in the study were adapted to the Turkish language through forward and backward translation and expert opinion. Content validity was assessed with a 2-week test-retest reliability, Cronbach's α reliability coefficient for stability, item-total correlation, and confirmatory factor analysis. Results: The scales showed good content validity (CVI = 0.95-0.99). Internal consistencies were acceptable to excellent (Cronbach's α =.79-.94), and moderate to good reproducibility estimates were observed (r =.67-.84). The MOEES factor structure also showed excellent fit. Conclusions: This study demonstrates that the adapted scales evaluated are valid and reliable for examining physical activity based on social cognitive processes in individuals surviving cancer in Türkiye. The scales examined in the study can be used to determine the cognitive factors affecting activity and to plan effective programs when providing physical activity counseling to individuals surviving cancer in Türkiye.
Keywords: Cancer Survivors; Physical Activity; Psychometrics; Social Cognitive Theories